Chapter 6 Voice of America Chinese-dialect broadcasting and the Chinese cultural Cold War, 1949-1953 - Taylor, Jeremy (Taylor & Francis, 2022)
This book explores contested notions of "Chineseness" in Southeast Asia and Hong Kong during the Cold War, showing how competing ideas about "Chineseness" were an important ideological factor at play in the region. After providing an overview of the scholarship on "Chineseness" and "Diaspora", the book sheds light on specific case studies, through the lens of the "Chinese cultural Cold War", from Hong Kong, Singapore, Malaya, Thailand, Indonesia and Vietnam. It provides detailed examples of competition for control of definitions of "Chineseness" by political or politically-oriented forces of diverse kinds, and shows how such competition was played out in bookstores, cinemas, music halls, classrooms, and even sports clubs and places of worship right across the region in the 1950s, 1960s and 1970s. The book also demonstrates how the legacies of these Cold War contestations continue to influence debates about Chinese influence -- and "Chineseness" -- in Southeast Asia and the wider region today.